Dynamic Model of a Horizontal Planetary Mill - Gennadiy M. Khves’ko; Petr E. Vaitekhovich; Denis N. Borovskiy (Механика машин, механизмов и материалов, 2022)
Issues are considered that are associated with the determination of dynamic loads encountered in moving units of the planetary mill. A horizontal planetary mill was chosen for compiling a dynamic model, as it has a great potential for organizing a closed grinding cycle with continuous loading and unloading of material. Calculation schemes were drawn up in moving units at the moments of the beginning of its operation and the steady movement of the grinding drums. Using the d’Alembert principle, taking into account the geometric parameters of the grinding unit, the reduced moments of inertia and moments of forces, as well as the acceleration time from a state of rest until the carrier reached a steady angular velocity, were determined. From the condition of equality of the power of the reduced moment of forces acting on the link of reduction, and the power of all forces and moments applied to the links of the planetary mill, the initial torque applied to the carrier was determined, which is necessary in the future to determine the power expended both at the moment of starting the mill, and at the time of its stable operation. It is shown that the initial torque depends on the value of the initial angular acceleration, which, in turn, can be different depending on the accepted law for changing the angular acceleration and the acceleration time to the required angular velocity of steady motion. It is also indicated that during the start-up period, the power supplied to the mill is spent on accelerating the rotation of the leading link and on overcoming various resistances such as friction forces in the units of the carrier and grinding drums.